2013
DOI: 10.2147/cia.s38589
|View full text |Cite
|
Sign up to set email alerts
|

Effects of person-centered care on residents and staff in aged-care facilities: a systematic review

Abstract: BackgroundSeveral residential aged-care facilities have replaced the institutional model of care to one that accepts person-centered care as the guiding standard of practice. This culture change is impacting the provision of aged-care services around the world. This systematic review evaluates the evidence for an impact of person-centered interventions on aged-care residents and nursing staff.MethodsWe searched Medline, Cinahl, Academic Search Premier, Scopus, Proquest, and Expanded Academic ASAP databases for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
310
0
24

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(345 citation statements)
references
References 23 publications
11
310
0
24
Order By: Relevance
“…또한 인간중심돌봄의 실천은 노인에게 제공되는 돌 봄의 질을 향상시키며 신체적 · 정서적 · 사회적 측면에서 노인의 삶의 질을 높여준다 [6,10]. 뿐만 아니라 노인요양시설에 대한 가족들의 만족도를 높이며, 직원들에게 직무의 만족도 증가, 이직률의 저하 등 긍정적인 효과가 있다 [9,10].…”
Section: 인간중심돌봄은 기존의 의료 및 치료 중심의 돌봄 보다는 거주 노 인의 개인적 특성을 이해하며 노인의 선택권unclassified
“…또한 인간중심돌봄의 실천은 노인에게 제공되는 돌 봄의 질을 향상시키며 신체적 · 정서적 · 사회적 측면에서 노인의 삶의 질을 높여준다 [6,10]. 뿐만 아니라 노인요양시설에 대한 가족들의 만족도를 높이며, 직원들에게 직무의 만족도 증가, 이직률의 저하 등 긍정적인 효과가 있다 [9,10].…”
Section: 인간중심돌봄은 기존의 의료 및 치료 중심의 돌봄 보다는 거주 노 인의 개인적 특성을 이해하며 노인의 선택권unclassified
“…Early research was hampered by poorly defined terms, small scale studies or a reliance on qualitative research methods and is of limited empirical value (Slater, 2006). In a recent systematic review of the evidence (Brownie and Nancarrow, 2013), person-centred care is reported to have a positive impact on staff job satisfaction (Lehuluante et al, 2012), staff capacity to meet the needs of patients (Brownie and Nancarrow, 2013), cost effectiveness (Olsson et al, 2009), better levels of staff autonomy and empowerment (Williams et al, 2007). For patients, significant improvements are reported in physical outcomes and reduction in boredom (Brownie and Nancarrow, 2013).…”
Section: Study Backgroundmentioning
confidence: 99%
“…In a recent systematic review of the evidence (Brownie and Nancarrow, 2013), person-centred care is reported to have a positive impact on staff job satisfaction (Lehuluante et al, 2012), staff capacity to meet the needs of patients (Brownie and Nancarrow, 2013), cost effectiveness (Olsson et al, 2009), better levels of staff autonomy and empowerment (Williams et al, 2007). For patients, significant improvements are reported in physical outcomes and reduction in boredom (Brownie and Nancarrow, 2013). However the bulk of the evidence is limited to older person settings and there are additional challenges to its implementation within acute hospital settings (Clisset et al, 2013).…”
Section: Study Backgroundmentioning
confidence: 99%
“…DCM aims at different levels: at the individual (residents and care givers), at the group (care giving teams) and at multidisciplinary teams and management (Van de Ven et al, 2013). Furthermore, person-centred methods, like DCM, are associated with (psychosocial) benefits for both people with dementia (whether or not with intellectual disability) and their care staff, by improving the quality of care (Brown et al, 2016;Brownie & Nancarrow, 2013;Edvardsson, Sandman, & Borell, 2014; Van der Meer, Nieboer, Finkenflügel, & Cramm, 2017;Willemse et al, 2015).…”
mentioning
confidence: 99%